2013
DOI: 10.1021/np400083k
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Lichen Secondary Metabolites against Plasmodium Liver Stage Parasites with FAS-II as the Potential Target

Abstract: Chemicals targeting the liver stage (LS) of the malaria parasite are useful for causal prophylaxis of malaria. In this study, four lichen metabolites, evernic acid (1), vulpic acid (2), psoromic acid (3) and (+)-usnic acid (4) were evaluated against LS parasites of Plasmodium berghei. Inhibition of P. falciparum blood stage (BS) parasites was also assessed to determine stage specificity. Compound 4 displayed the highest LS activity and stage specificity (LS IC50 value 2.3 μM, BS IC50 value 47.3 μM). The compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 66 publications
0
55
0
Order By: Relevance
“…Another study on the protective effect of PSA was carried out on mice and the gastric protective effect of PSA was determined (Sepulveda et al 2013). In the studies related with toxic concentrations of PSA, inhibition of growth as determined in different bacteria species (Celenza et al 2013;Mitrović et al 2014), liver parasites (Lauinger et al 2013) and some cancer cells (Correcché et al 2004;Brandao et al 2013) exposed to PSA. In addition, Correcché et al (2004) revealed that PSA significantly showed apoptotic activity on hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on the protective effect of PSA was carried out on mice and the gastric protective effect of PSA was determined (Sepulveda et al 2013). In the studies related with toxic concentrations of PSA, inhibition of growth as determined in different bacteria species (Celenza et al 2013;Mitrović et al 2014), liver parasites (Lauinger et al 2013) and some cancer cells (Correcché et al 2004;Brandao et al 2013) exposed to PSA. In addition, Correcché et al (2004) revealed that PSA significantly showed apoptotic activity on hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Glycyrrhetic acid (Figure 4) has exhibited notable (IC50 1.69 μg/mL) in vitro antiplasmodial activity against P. falciparum, and docking studies (Discovery Studio) have also shown glycyrretic acid to dock moderately well to P. falciparum lactate dehydrogenase [414]. (+)-Usnic acid, a secondary metabolite from lichen, was identified as an active and selective inhibitor of the liver stage form of Plasmodium berghei by Lauinger and co-workers [415]. In the molecular docking study to identify the binding affinities and binding sites of (+)-usnic acid and three other lichen secondary metabolites (evernic acid, vulpic acid, and psoromic acid, Figure 16) with Plasmodium type II fatty acid biosynthesis pathway (FAS-II) enzymes, these workers found that the mechanism of action of lichen acids on FAS-II may be different from those of previously described FAS-II enzymes inhibitors.…”
Section: Plasmodium Targetsmentioning
confidence: 99%
“…The modeling study they carried out indicated that those compounds appear to inhibit FAS-II enzymes indirectly via binding to allosteric sites on the protein surface and not to the active sites of FAS-II enzymes. This indirect binding is speculated to possibly affect the enzyme conformations and subsequently interfere with the catalytic activities [415].…”
Section: Plasmodium Targetsmentioning
confidence: 99%
“…It is shown to exert a number of biological activities including anti-inflammatory, analgesic and antipyretic, antibiotic, antiviral, antimicrobial, antiproliferative, gastroprotective, antitumor, antioxidant, antimycotic, antigrowth and antiinsect properties [22,23] . Although few studies [9,[24][25][26][27] dealing with antiprotozoal effect of usnic acid are available, its anticoccidial effect is largely unknown. The present experiment was set out to investigate therapeutic action of usnic acid against coccidiosis in broilers.…”
Section: öZetmentioning
confidence: 99%
“…De Carvalho et al [24] investigated the effects of usnic acid against Trypanosoma cruzi epimastigotes and trypomastigotes, and reported that usnic acid treatment resulted in growth inhibition in a dose-dependent manner. Lauinger et al [26] reported antiplasmodial effect of some lichen compounds (e.g., evernic acid, vulpic acid, psoromic acid and (+)-usnic acid) against liver stages of Plasmodium berghei.…”
Section: Feed Conversion Ratio (Fcr Feed: Bw Gain)mentioning
confidence: 99%